2010
DOI: 10.13073/0015-7473-60.5.440
|View full text |Cite
|
Sign up to set email alerts
|

Various Factors and Propagation Trends of Stress Waves in Cross Sections of Euphrates Poplar

Abstract: Various factors and propagation trends of stress waves in cross sections of wood need study to improve accuracy in the quality evaluation of wood and decay detection in standing trees. In this study, a Fakopp Microsecond Timer was used to measure the stress wave transmission time of Euphrates poplar (Populus euphratica Oliv.). Velocity was calculated to find the trend and make wavefront maps of stress waves. Results indicated that stress waves travel fastest in the radial direction and that velocity decreased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Compared to all the other low values of the speeds, sometimes they have nothing to do with internal defects, as the wood is healthy. However, in the tangential direction, the propagation velocities are lower than those on the radial direction (Beldeanu 2008;Lin et al 2008;Kazemi et al 2009;Liang et al 2010;Feng et al 2014). In addition, the sections in which these values were recorded have an oval shape, which further supports the claims that the propagation velocities are closely related to the anatomical structure of the wood (Feng et al 2014;Alves et al 2015) and that an uneven width of the annual rings influences the density of the wood (Filipovici 1964;Sandoz and Lorin 1996;Beldeanu 2008).…”
Section: Speed Of Propagation and Resistance To Penetrationmentioning
confidence: 68%
“…Compared to all the other low values of the speeds, sometimes they have nothing to do with internal defects, as the wood is healthy. However, in the tangential direction, the propagation velocities are lower than those on the radial direction (Beldeanu 2008;Lin et al 2008;Kazemi et al 2009;Liang et al 2010;Feng et al 2014). In addition, the sections in which these values were recorded have an oval shape, which further supports the claims that the propagation velocities are closely related to the anatomical structure of the wood (Feng et al 2014;Alves et al 2015) and that an uneven width of the annual rings influences the density of the wood (Filipovici 1964;Sandoz and Lorin 1996;Beldeanu 2008).…”
Section: Speed Of Propagation and Resistance To Penetrationmentioning
confidence: 68%
“…, where  is the ray angle, represents the azimuth of the v radial direction relative to the axis of the coordinate system, and  specifies the degree of anisotropy. Liang et al (2010) showed that stress waves traveled fastest in radial direction and that velocity decreased as the wave propagation path shifted toward to tangential direction. Velocity also increased as the number of annual rings increased.…”
Section: Introductionmentioning
confidence: 99%